Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1269/jrr.10114
|View full text |Cite
|
Sign up to set email alerts
|

Intercellular Communication Amplifies Stressful Effects in High-Charge, High-Energy (HZE) Particle-Irradiated Human Cells

Abstract: Understanding the mechanisms that underlay the biological effects of particulate radiations is essential for space exploration and for radiotherapy. Here, we investigated the role of gap junction intercellular communication (GJIC) in modulating harmful effects induced in confluent cultures wherein most cells are traversed by one or more radiation tracks. We focused on the effect of radiation quality (linear energy transfer; LET) on junctional propagation of DNA damage and cell death among the irradiated cells.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
22
0

Year Published

2012
2012
2015
2015

Publication Types

Select...
7
1

Relationship

5
3

Authors

Journals

citations
Cited by 20 publications
(27 citation statements)
references
References 33 publications
5
22
0
Order By: Relevance
“…In this context, our studies have shown that the magnitude of the effects due to connexin channels in enhancing or reducing the propagation of radiation-induced oxidative stress is a function of radiation quality (LET effect). The abundance of reactive species along the track of an HZE particle may be the factor that affects permeability of connexin channels (9)(10)(11). These results are consistent with earlier studies showing that the cellular redox environment together with gap junction communication are the major mediators of the propagation of stressful responses from a particle-irradiated cells to bystander cells in the vicinity (13,17,201,308).…”
Section: Propagation Of Hze Particle-induced Oxidative Damage To Nontsupporting
confidence: 89%
“…In this context, our studies have shown that the magnitude of the effects due to connexin channels in enhancing or reducing the propagation of radiation-induced oxidative stress is a function of radiation quality (LET effect). The abundance of reactive species along the track of an HZE particle may be the factor that affects permeability of connexin channels (9)(10)(11). These results are consistent with earlier studies showing that the cellular redox environment together with gap junction communication are the major mediators of the propagation of stressful responses from a particle-irradiated cells to bystander cells in the vicinity (13,17,201,308).…”
Section: Propagation Of Hze Particle-induced Oxidative Damage To Nontsupporting
confidence: 89%
“…For example, early and late generation of radiation-induced mitochondrial ROS/RNS mediates changes in mitochondrial DNA copy number [141], mutations [142] and gene expression [143; 144], autophagy [145; 146], apoptosis [147; 148; 149], propagation of non-targeted responses [73; 150; 151; 152; 153; 154; 155], the induction of nuclear DNA damage [156], genomic instability [157], neoplastic transformation [158], and degenerative conditions [37; 63; 159] among other outcomes [2; 37]. We investigated effects of ionizing radiation on mitochondrial protein import, assembly of large protein complexes, protein oxidation and activity of metabolic and antioxidant enzymes [10; 11; 45; 48; 160; 161]. Significantly, the persistence of radiation effects that lead to mitochondrial dysfunction in progeny cells has serious consequences to health risks [2; 162].…”
Section: Mitochondria and Delayed Effects Of Ionizing Radiationmentioning
confidence: 99%
“…The patterns of radiation exposure that arise as a consequence of these properties can be highly non-uniform, and lead to conditions that are favorable for eliciting radiation-induced bystander effects. As summarized in a recent review (Blyth and Sykes 2011), many studies have provided strong evidence to support the existence of a variety of radiation-induced bystander effects (Brooks et al 1974, Nagasawa and Little 1992, Mothersill and Seymour 1997, Azzam et al 1998, Wright 1998, Zhou et al 2000, Autsavapromporn et al 2011, Buonanno et al 2011). These effects may be toxic or protective in cells that are not directly irradiated; they can result from a variety of signals from neighboring irradiated cells (Wright and Coates 2006).…”
Section: Introductionmentioning
confidence: 99%